Implementing Snack Food Composition Label Analysis for Numeracy Learning in Elementary School: A Study in Teacher Professional Education - Siti Maryam Rohimah; Dadang Iskandar; Eggie Nugraha; Taufiqulloh Dahlan; Yuni Indriyani; Siti Maryam Rohimah; Dadang Iskandar; Eggie Nugraha; Taufiqulloh Dahlan (Universitas Negeri Malang, 2026)
The use of authentic contexts in numeracy learning is important to help prospective elementary school teachers design meaningful and contextual mathematics instruction. However, a gap remains in the literature regarding how prospective teachers perceive the feasibility and potential of authentic context-based numeracy activities. This study aimed to explore how elementary student teachers in a Teacher Professional Education (TPE) program perceive the feasibility and potential of implementing the activity